Identifikasi dan Preservasi Digital Manuksrip Turots oleh TIM Nahdlatut Turots dan Turots Center Universitas Yudharta di Wilayah Pasuruan - Rifqi, Ach. Nizam; Puspita, Anindya Gita (Pustakaloka, 2024)
Turots have important value for the Indonesian people because apart from containing Islamic religious teachings, they also contain history. Awareness of the importance of turots can be seen from digital identification and preservation activities carried out by Nahdlatut Turots and Turots Center Yudharta University Pasuruan (UYP). This research aims to identify and understand the process of Digital Preservation of Turots carried out by Nahdlatut Turots and Turots Center UYP. The method used in this research is descriptive qualitative with a case study approach. This research focuses on manuscripts, namely turots of the works of ulama which have been written by the UYP Turots Center in collaboration with Nahdlatut Turots. Interview methods and observation methods were used to collect data in the field. This research shows that Nahdlatut Turots and the UYP Turots Center carry out digital identification and preservation starting by conducting turots searches. After getting the turots, identification is carried out both physically and by lineage. Next, cataloging is carried out to describe the turot. The turots team then preserved the turots and digitized them. The digital turots files are then published in Turots Corner.